La soggettività femminile nel Romanzo della fanciulla di Matilde Serao - Laricchia, Giorgia (Status Quaestionis, 2017)
The analysis of Matilde Serao’s Il romanzo della fanciulla is intended to detect stylistic and rhetoric choices – impersonality, autobiographical elements, focalizations, free indirect style – through which the author represents the female subjectivity. The comparative study between Serao and Verga highlights what the former borrows from the latter: in Il romanzo della fanciulla we recognise the same axiom of the preface to I Malavoglia, the struggle for life. But in Serao’s work this naturalistic principle inherited by Darwin is applied only to women.